Measuring judicial independence in international law: Putting together the pieces of the puzzle. Issue 4 (August 2017) - Dimitropoulos, Georgios
This article searches for paths, frameworks and modules for the measurement and evaluation of judicial independence in international law. First, it discusses the measurability of the concept. Judicial independence, both as such and especially at the international level, is very difficult to measure, given the ambivalence of some proxies and variables that have been used in empirical research in order to measure it, and given the competing interests and actors in international adjudication: independence does not stand alone as the only value that needs to be protected in international adjudication. Second, the article presents methodologies for the evaluation of international judicial independence. The three competing methodologies are (i) the subjective, which looks at the subjective perception of the judges themselves or the public; (ii) the output-based, which looks at the decisions of the courts and tribunals; and (iii) the institutional, which looks at the personal independence guarantees of the judge, and the organizational safeguards of independence. Finally, this article presents its preferred model for the measurement of international judicial independence. The study takes an institutional-psychological approach that focuses on the judge and the individual institutions.